PENERAPAN PEDEKATAN TAKTIS DALAM MENINGKATKAN PASSING-CONTROL PADA PESERTA UKM FUTSAL - Agung Gunawan (STKIP Muhammadiyah Kuningan, 2021)
The purpose of this study was to determine the effect of applying a tactical approach to the passing-control of futsal players at STKIP Muhammadiyah Kuningan. This study uses experimental research methods. The population and sample in this study were UKM Futsal players from STKIP Muhammadiyah Kuningan with a population of 50 people and a sample of 20 people and the sampling technique used was random sampling. The research instrument used in this study was the Pass-Control test. The results of the analysis and processing of the Pre-Test data obtained the lowest time of 10, the highest time of 15. While the Post-Test data obtained the lowest time of 13, the highest time of 17. Based on the calculation results, there is a significant difference between the passing-control abilities of the participants of the UKM Futsal players from STKIP Muhammadiyah Kuningan. Keywords: Tactical Approach, Passing-Control, Futsal.